2015
DOI: 10.1007/s12522-015-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

The development of surgical sperm extraction and new challenges to improve the outcome

Abstract: Surgical sperm extraction with intracytoplasmic sperm injection has become widespread worldwide and is regarded as the sole option for patients with azoospermia. However, the sperm retrieval rate remains unsatisfactorily low, particularly for men with non-obstructive azoospermia (NOA). Therefore, the technical challenges associated with improving the sperm retrieval rate for men with NOA are being addressed. The most successful method developed to date is microdissection testicular sperm extraction (micro-TESE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 113 publications
0
6
1
1
Order By: Relevance
“…The first description of testicular sperm for use in assisted reproduction occurred in 1993 [ 13 ]. Successful fertilization, embryo development, implantation and pregnancy was considered to be an unanticipated result by some reproductive experts given the expected need for additional maturation by sperm that was known to occur during epididymal transit [ 14 ].…”
Section: History Of Surgical Sperm Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…The first description of testicular sperm for use in assisted reproduction occurred in 1993 [ 13 ]. Successful fertilization, embryo development, implantation and pregnancy was considered to be an unanticipated result by some reproductive experts given the expected need for additional maturation by sperm that was known to occur during epididymal transit [ 14 ].…”
Section: History Of Surgical Sperm Retrievalmentioning
confidence: 99%
“…This success was revolutionary for the treatment of men with NOA, but certain challenges remained given the sporadic, almost anecdotal, success of initial efforts to treat men with NOA who were previously considered to be sterile [ 16 ]. Based on observations that limited sperm was retrieved during simple biopsy, it was originally thought that multiple testis biopsies would increase the chance of retrieval as sperm production was believed to occur in isolated areas in the testis of men with NOA and spermatogenic failure [ 14 ]. In reality, multiple open biopsies resulted in removal of large quantities of testicular tissue and created a new risk, namely of harm to the blood supply of the testis from multiple incisions on the tunica albuginea.…”
Section: History Of Surgical Sperm Retrievalmentioning
confidence: 99%
“…Various medical treatments are suggested for NOA men before micro-TESE to achieve a high sperm retrieval rate. Among the suggested treatments, clomiphene citrate (CC) is a selective estrogen receptor modulator that competitively binds the estrogen receptor in the hypothalamus and increases the level of FSH and LH, ultimately increasing the success of sperm retrieval rate by micro-TESE (15). However, a study showed that Clomiphene administration did not affect the success of sperm extraction (16).…”
Section: Introductionmentioning
confidence: 99%
“…(Kumar, 2013). NOA is either due to primary testicular impairment or secondary to pituitary insufficiency and subsequently inadequate gonadotropin production (Enatsu et al., 2015). In addition to hormonal replacement therapy (HRT) when indicated, management of patients with NOA involves testicular sperm extraction (TESE or microdissection TESE) and subsequent intracytoplasmic sperm injection (ICSI) (Abdel Raheem et al., 2013).…”
Section: Introductionmentioning
confidence: 99%